Constructing multifunctional nanofiller with reactive interface in PLA/CB-g-DOPO composites for simultaneously improving flame retardancy, electrical conductivity and mechanical properties. (1st March 2020) - Wen, Xin; Liu, Zhiqi; Li, Zhi; Zhang, Jing; Wang, De-Yi; Szymańska, Karolina; Chen, Xuecheng; Mijowska, Ewa; Tang, Tao
Abstract: Multifunctional polymer nanocomposites are one of the hottest topics in the field of materials science. Herein nanosized carbon black (CB) was functionalized by H2 O2 hydroxylation and chemical grafting of phosphorous flame retardant. The obtained nanofiller hybrids (CB- g -DOPO) presented a high grafting degree to 37.89 wt%, and remained large numbers of active hydroxyl groups (CH–OH), which could covalently react with adscititious compatibilizer to promote its dispersion and interaction with poly(l -lactide) (PLA) matrix. The resultant PLA nanocomposites showed remarkably improved flame retardancy, electrical conductivity and mechanical properties. The limited oxygen index (LOI) was 29.3%; the UL-94 rating reached to V0; and the peak of heat release rate (PHRR) was decreased by 50% in cone calorimeter testing. Outstanding electrical conductivity was present with more than 4 wt% CB- g -DOPO. Besides, the nanocomposites displayed a good balance on stiffness and toughness, especially 8.7 and 2.5 times improvement on elongation at break and impact strength, respectively. The enhancement mechanism was discussed on the basis of the unique structure and surface composition of CB- g -DOPO. This work will be favorable to the designation and application of multifunctional polymer nanocomposites with high performances. Graphical abstract: Image 1